Nature of Responsibility of Regional Heads in the Organization of Regional Government - Ramadhan, Muhammad Rohady (Pancasila International Journal of Applied Social Science, 2023)
The accountability of Regional Heads in regional government is a fundamental aspect that cannot be ignored. This is a realisation of the authority they receive and plays a key role in preventing abuse of authority. This responsibility includes strategic decision-making, budget management, and implementation of policies that affect society at the regional level. In this case, accountability is a defence against potential abuse of authority and violations of the principles of good governance. This is also related to transparency and accountability, allowing the public to monitor Regional Heads' actions closely. This accountability also reflects democratic principles where public officials, including Regional Heads, are responsible to the communities they serve. To carry out accountability effectively, a strong legal framework is needed that regulates the nature and mechanisms of accountability. This includes regulations and laws that regulate the duties and responsibilities of Regional Heads. Thus, the accountability of Regional Heads is an integral element in maintaining a regional government that is effective, transparent and by democratic principles.